Karyotype is an independent prognostic factor in adult acute lymphoblastic leukemia (ALL): analysis of cytogenetic data from patients treated on the Medical Research Council (MRC) UKALLXII/Eastern Cooperative Oncology Group (ECOG) 2993 trial. - Moorman, A; Harrison, C; Buck, G; Richards, S; Secker-Walker, L; Martineau, M; Vance, G; Cherry, A; Higgins, R; Fielding, A; Foroni, L; Paietta, E; et al. (2007)
Pretreatment cytogenetics is a known predictor of outcome in hematologic malignancies. However, its usefulness in adult acute lymphoblastic leukemia (ALL) is generally limited to the presence of the Philadelphia (Ph) chromosome because of the low incidence of other recurrent abnormalities. We present centrally reviewed cytogenetic data from 1522 adult patients enrolled on the Medical Research Council (MRC) UKALLXII/Eastern Cooperative Oncology Group (ECOG) 2993 trial. The incidence and clinical associations for more than 20 specific chromosomal abnormalities are presented. Patients with a Ph chromosome, t(4;11)(q21;q23), t(8;14)(q24.1;q32), complex karyotype (5 or more chromosomal abnormalities), or low hypodiploidy/near triploidy (Ho-Tr) all had inferior rates of event-free and overall survival when compared with other patients. In contrast, patients with high hyperdiploidy or a del(9p) had a significantly improved outcome. Multivariate analysis demonstrated that the prognostic relevance of t(8;14), complex karyotype, and Ho-Tr was independent of sex, age, white cell count, and T-cell status among Ph-negative patients. The observation that Ho-Tr and, for the first time, karyotype complexity confer an increased risk of treatment failure demonstrates that cytogenetic subgroups other than the Ph chromosome can and should be used to risk stratify adults with ALL in future trials.